Implications of Residue Quantity and Quality on Rotational Maize Productivity - International Institute of Tropical Agriculture (International Food Policy Research Institute, 2023)
Retaining crop residues in fields is a pathway to build soil organic matter (SOM) on smallholder farmers. The quality of crop residues can be improved through integrating more legume residues. This experiment assess the effect of legume residues from a doubled up system as compared to maize residues on rotational maize and N dynamics in the short term. In the long term, this can increase both quantity and quality of SOM.